Effects of cognitive behavioral therapy on improving depressive symptoms and increasing adherence to antiretroviral medication in people with HIV - Qin, Keke; Zeng, Jiale; Liu, Li; Cai, Yumei (Frontiers in Psychiatry, 2022)
The incidence of depression is higher in PLWH (people living with HIV) than in the general population. It is of clinical significance to explore effective measures to improve depression in patients. But the available evidence is still quite limited. CBT is considered to be one of the effective methods to improve depression, medication adherence and quality of life in PLWH. Therefore, this study aimed to systematically evaluate the effect of cognitive behavioral therapy on improving depressive symptoms and increasing adherence to antiretroviral therapy (ART) in people living with HIV. The Cochrane Library, Embase, PubMed and Web of Science databases were searched by computer to collect randomized controlled trials on the effects of cognitive behavioral therapy on improving depression and increasing ART medication adherence in PLWH, and the retrieval time was from the inception of each database to January 10, 2022. Meta-analysis was performed by two researchers using Stata 15.0 software after screening the literature, extracting data and evaluating quality according to inclusion and exclusion criteria. A total of 16 studies with 1,998 patients were included. Meta-analysis results showed that CBT improved depressive symptoms in PLWH (SMD= -0.09, 95% CI [-0.13 to-0.04], P<0.001) with better long-term (<6 months) depression improvement (SMD= - 0.09, 95%CI [-0.15 to -0.02], P=0.006) than short-term(0 to 6 months); the difference in improved ART medication adherence in the CBT group compared to the control group was not statistically significant (SMD= 0.04, 95% CI [-0.06 to 0.13], P=0.490). There may be publication bias due to incomplete inclusion of literature as only published literature was searched. Cognitive behavioral therapy is effective in improving depressive symptoms in people living with HIV, with better long-term results.